2016
DOI: 10.1159/000439492
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal High Protein Intake Can Contribute to Accelerated Weight Gain of Infants and Increased Obesity Risk

Abstract: Worldwide, 38% of women are now overweight (BMI 25-30) or obese (BMI ≥30). There is increasing evidence that maternal obesity can result in unfavorable (epigenetic) pre- and postnatal programming of important genes of the offspring. Infants of overweight mothers show faster weight gain during infancy, which is associated with higher risk of obesity during childhood and adult life. This can have lifelong consequences such as increased risk of noncommunicable diseases. Many studies indicate that infants of obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
2
27
0
1
Order By: Relevance
“…A randomized controlled trial [17] indicated that infants fed a whey-based formula with a protein content of 1.8 g/100 kcal have growth and metabolic outcomes that are similar to those of breastfed infants through 4 months of age. A meta-analysis (n = 1,150 infants) recently confirmed that at 4 months of age the weight of infants fed the 1.8 g/100 kcal formula corresponds to the median of the WHO standard [15] . The formula tested in those studies had an amino acid pattern that was close to the pattern in breast milk [15] .…”
Section: Protein Intake -Long-term Outcomes and Biomarkersmentioning
confidence: 92%
See 3 more Smart Citations
“…A randomized controlled trial [17] indicated that infants fed a whey-based formula with a protein content of 1.8 g/100 kcal have growth and metabolic outcomes that are similar to those of breastfed infants through 4 months of age. A meta-analysis (n = 1,150 infants) recently confirmed that at 4 months of age the weight of infants fed the 1.8 g/100 kcal formula corresponds to the median of the WHO standard [15] . The formula tested in those studies had an amino acid pattern that was close to the pattern in breast milk [15] .…”
Section: Protein Intake -Long-term Outcomes and Biomarkersmentioning
confidence: 92%
“…A meta-analysis (n = 1,150 infants) recently confirmed that at 4 months of age the weight of infants fed the 1.8 g/100 kcal formula corresponds to the median of the WHO standard [15] . The formula tested in those studies had an amino acid pattern that was close to the pattern in breast milk [15] .…”
Section: Protein Intake -Long-term Outcomes and Biomarkersmentioning
confidence: 92%
See 2 more Smart Citations
“…Composition of infant formulas has evolved with increasing knowledge of BM. Recently, a pooled analysis of individual growth data (11 clinical trials; n = 1,882 [15] ) of infants who received a modified whey-based low-protein starter formula (1.8 g protein/100 kcal) [16] with an amino acid profile close to term BM [17] has become available. The weight and length of formula-fed infants at 4 months correspond to the 50th percentile of the WHO global growth standard [18] .…”
Section: Protein Needs For Growthmentioning
confidence: 99%